The effect of various nickel oxide ratios on the color and reflectivity of PY53 nickel-titanate yellow pigment - Aslan, Emre; Toy, Emre; Guner, Zeynep; Grijalbo, Alejandro; Yesilci, Emine; Cicek, Bugra (ELSEVIER, 2022)
Complex inorganic nickel-titanate PY53 yellow pigments with a high thermal solar reflectance were synthesized. Four different compositions were made with increasing nickel oxide (NiO) ratios, with Sb2 O3 and TiO2 as the fixed components. Mixtures were prepared by adding excess NiO of 0/2/4/6 wt%. Excess 6 wt% NiO gives a maximum near infrared solar reflectance of 55.2%. The reflectance (%R) analysis of the pigments was measured with a reflection spectrophotometer. Pigment powders were used as reflective material in a polymer matrix. The chemical composition of the pigments was determined using an X-ray Fluorescence Spectrometer (XRF). The crystal structure of the pigments was analyzed using X-ray Diffraction (XRD) measurements. The distribution and particle structure of the particles were determined using a scanning electron microscope (SEM). The particle size distribution (PSD) was characterized by measuring with a laser diffraction particle size analyzer. The PY53 yellow pigment colors were measured using the CIE L*a*b* color index. The PY53 yellow pigment was milled, using a Rosetti mill, into the same particle sizes to decrease the effects of the milling process on its properties. The yellowness (*b) increased as the NiO ratio increased in all applications. Excess 6 wt% NiO gives a maximum yellowness value polymer matrix 50.8%. The newly synthesized PY53 yellow pigment can be used in con-struction, for enamel coatings with its high reflectivity performance, for comfortable clothing, and for durable properties in plastic products.
Keywords: NiO; Color tone; Solar reflectance; OPTICAL-PROPERTIES; PARTICLE-SIZE; SOLAR; REFLECTANCE; COATINGS; Chemistry